Eliminating Postoperative Nausea and Vomiting in Outpatient Surgery with Multimodal Strategies including Low Doses of Nonsedating, Off-Patent Antiemetics: Is “Zero Tolerance“ Achievable? - Susan J. Skledar; Brian A. Williams; Manuel C. Vallejo; Patricia L. Dalby; Jonathan H. Waters; Ronald Glick; Michael L. Kentor (The Scientific World Journal)
For ondansetron, dexamethasone, and droperidol (when used for prophylaxis), each is estimated to reduce risk of postoperative nausea and/or vomiting (PONV) by approximately 25%. Current consensus guidelines denote that patients with 0–1 risk factors still have a 10–20% risk of encountering PONV, but do not yet advocate routine prophylaxis for all patients with 10–20% risk. In ambulatory surgery, however, multimodal prophylaxis has gained favor, and our previously published experience with routine prophylaxis has yielded PONV rates below 10%. We now propose a “zero-tolerance” antiemetic algorithm for outpatients that involves routine prophylaxis by first avoiding volatile agents and opioids to the extent possible, using locoregional anesthesia, multimodal analgesia, and low doses of three nonsedating off-patent antiemetics. Routine oral administration (immediately on arrival to the ambulatory surgery suite) of perphenazine 8 mg (antidopaminergic) or cyclizine 50 mg (antihistamine), is followed by dexamethasone 4 mg i.v. after anesthesia induction (dexamethasone is avoided in diabetic patients). At the end of surgery, ondansetron (4 mg i.v., now off-patent) is added. Rescue therapy consists of avoiding unnecessary repeat doses of drugs acting by the same mechanism: haloperidol 2 mg i.v. (antidopaminergic) is prescribed for patients pretreated with cyclizine or promethazine 6.25 mg i.v. (antihistamine) for patients having been pretreated with perphenazine. If available, a consultation for therapeutic acupuncture procedure is ordered. Our approach toward “zero tolerance” of PONV emphasizes liberal identification of and prophylaxis against common risks.